HYPOLIPIDEMIC EFFECT OF CHLOROGENIC ACID IN A HYPERCHOLESTEROLEMIC RAT MODEL - NISHI,; AMJID AHAD,; PAWAN KUMAR, (International Journal of Pharma and Bio Sciences, 2013)
Cardiovascular diseases continue to be a leading cause of morbidity and mortality in developed as well as developing countries. Hypercholesterolemia is one of the factors that have contributed in acceleration of Coronary Heart Diseases in India. It is associated with elevated lipid levels in the blood. Treatment of hypercholesterolemia is one of the major approaches towards decelerating the atherogenic process. Currently available hypolipidemic drugs have been associated with number of side effects. Hypolipidemic activity of chlorogenic acid was studied against cholesterol induced hypercholesterolemia in male Wistar rats. Chlorogenic acid was administered at doses of 10 mg/ kg body weight (intravenous: i.v.), 20 mg/kg bw (i.v.) and 50mg/kg body weight (i.v.) to the cholesterol induced hypercholesterolemic rats. Chlorogenic acid showed a significant decrease in the levels of serum cholesterol, triglyceride, LDL-C, VLDL-C and significant increase in the level of serum HDL-C.